National Identity and the European Union : case study of Brexit - Etijoro, Leslie Oghenekaro; Rolenc, Jan Martin, 1980-; Doležal, Tomáš; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2017)
since the origin of the European it has experienced different challenges ranging from security, migration, terrorism, and economic issues. However, there is a challenge that is imminent and more threatening to the European Union, Nationality of its member-states. the challenge of nationality has plagued the E.U. and this research intend to analyse the impact of nationality in the context of Brexit.The main question here is the analysis of the impact of nationality in the British policy of Brexit. What and how did nationality influence the Brexit. And also a quantitative and a qualitative analysis of the British-E.U. policy before the Brexit.Literature, Books1. Bruyn, S.T. (2005). A Civil Republic Beyond Capitalism and Nationalism. Bloomfield, CT, Kumarian Press.2. Viotti, P.R., & Kauppi, M. V. (2008). International Relations and World Politics, Security, Economy, Identity. Harlow, Prentice Hall.3. Woodwell, D. (2007). Nationalism in International Relations, Norms, Foreign Policy, and Enmity. New York, Palgrave Macmillan.Articles1. Ashcroft, R., & Bevir, M. (2016). Pluralism, National Identity and Citizenship:Britain after Brexit. The Political Quarterly, Vol. 87, (No. 3), 355to359.2. Fontana, C. G., & Parsons, C. (2014). One Womans Prejudice: Did Margaret Thatcher Cause Britains Anti Europeanism? Journal of Common Market Studies, Vol. 53(No. 1), 89to105.3. Goodwin, M. J. & Heath, O. (2016). The 2016 Referendum, Brexit and the LeftBehind, An Aggregate-level Analysis of theResult. The Political Quarterly Vol. 87, (No. 3), 323to332.4. Henderson, A. & McEwen N. (2005). Do Shared Values Underpin National Identity? Examining the Role of Values in National Identity in Canada and the United Kingdom. National Identities, 7(2) 173to191.5. Martin, A. K. (2012). National Identity Infrastructures, Lessons from the United Kingdom. IFIP Advances in Information and Communication Technology Volume 386 of the series. 44to55.6. Oliver, T. (2015).
To be or not to be in Europe: is that the question? Britains European question and an in/out referendum. International Affairs, Vol. 91(No. 1), 77to91.7. Whitman R. G. (2016). Brexit or Bremain, What Future for the UKs European Diplomatic Strategy? International Affairs Vol. 92(No. 3) 509to529.MethodologyQuantitative and qualitative content analysis
Vedoucí práce: Jan Martin Rolenc
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor dipl. práce]; diplomové práce; master's theses